PENGARUH MODEL PEMBELAJARAN QUESTION STUDENT HAVE DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KEWIRAUSAHAAN KELAS XI SMK SWASTA GKPS 2 PEMATANGSIANTAR - Loly Yenti; Benjamin Albert Simamora (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine the influence of the Question Student Have learning model and learning interest on student learning outcomes in class X1 entrepreneurship subjects of SMK Swasta GKPS 2 Pematangsiantar, which was carried out with statistical tests both partially and simultaneously. This research uses an experimental method with a quantitative approach. The population in this study was the entire class XI totaling 127 students, with the sample being class XI TBSM-1 with 30 students as an experimental class and TBSM-2 with a total of 30 students as a control class, sample selection using the judgment sampling technique. Data collection techniques using observation, interviews, questionnaires, and tests. Meanwhile, the data analysis techniques used are normality tests, simple linear regression tests, hypothesis tests using multiple linear regression, coefficients of determination, T-tests, and F-tests using the SPSS application version 26.Based on the results of data analysis using hypothesis testing t, calculate for X1 = 2.130 and t-table (at a significant level of 5%) = 2.052 and obtained calculate for X2 = 2.123 and t-table (at a significant level of 5%) = 2.052 means calculate> t-table. According to the criteria, H0 is accepted if tcount < t-table, and H0 is rejected if tcount > t-table. F test results with a sig level of < 0.05 with a value of 9.018 > 3.35 So, it can be concluded that there is an Influence of the Question Student Have Learning Model and learning interest on student learning outcomes in class X1 entrepreneurship subjects of Private Vocational School GKPS 2 Pematangsiantar